What culture is your university? Have universities any right to teach entrepreneurialism?. Issue 1 (3rd January 2020) - Bamber, Christopher John; Elezi, Enis
Abstract : Purpose: The purpose of this paper is to discuss the need for universities to develop an entrepreneurial culture and assess higher education practitioners' opinions of the culture of the university they are working in. Design/methodology/approach: The research provides empirical data collected through a survey instrument originally used for a PhD research study; however, this paper focuses on the question set related to culture, which was based on the organisational culture model presented by Quinn in 1988. Findings: The findings indicate that a number of respondents reported from a heterogeneous population of higher education institutes predominantly responded they were working within a hierarchy cultural type with many reporting a market cultural type. While respondents from a homogeneous group from a single university reported in the main they were working in a market-driven cultural type with the next main category being a clan culture. Research limitations/implications: The study population reported in the main that there is predominantly a market culture in UK universities. However, this research has focussed entirely on respondents working within the UK HE sector, thus, has ignored potential differences that could be present within the global HE emerging markets. Originality/value: The paper strengthens understanding of the critical importance of innovation and entrepreneurship in universities. Students, scholars, HE policy makers and HE practitioners can gather a range of insights pointed at university culture and rest assured in the main they are market focussed.